(3YbdGA GdeLGfjfs - (3GdMSf Hf eMeO Hf MHjH Hf CjhH CHh GdbGSe GdfjSGHhQj,J (B406 (3g` s ((3CHhHcQ ESeGYjd Hf EHQGgje Hf OQY GddNej s)
(3ChdgG (B:s
(3ehJ hYRG HdG Pd, hZfi HdG abQ hGNJda GdfGS ajgG ef KdGKjf hLgI, hCTGQ CHhHcQ eMeO Hf YeQ GdhQGb Edi eG PcQfG s
(3BNQgG (B:s
(3hbO hba Ydi GdMSjf Hf efUhQ, abGd dg GdMSjf(B: (3TgOJ GdfGQ hGdLf` `I hGdCedGc hGdcQSj s
(3fSNI KGfjIs
(3hjJab BNQgG eY GdfSNI GdChdi HGNJdGa HYV GdCdaGXs
(3fhGOQ hCTYGQ hCNHGQ Yf GdMebi hGdeLGfjf ef GdPchQ hGdEfGKs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs